(untitled) (Communications in Computational Physics, 2022)
A coupling framework that leverages the advantages of the diffuse and sharp interface immersed boundary (IB) methods is presented for handling the interaction among particles and particles with the static complex geometries of the environment. In the proposed coupling approach, the curvilinear IB method is employed to represent the static complex geometries, a variant of the direct forcing IB method is proposed for simulating particles, and the discrete element method is employed for particle-particle and particle-wall collisions. The proposed approach is validated using several classical benchmark problems, which include flow around a sphere, sedimentation of a sphere, collision of two sedimenting spheres, and collision between a particle and a flat wall, with the present predictions showing an overall good agreement with the results reported in the literature. The capability of the proposed framework is further demonstrated by simulating the interaction between multiple particles and a wall-mounted cylinder, and the particle-laden turbulent flow over periodic hills. The proposed method provides an efficient way to simulate particle-laden turbulent flows in environments with complex boundaries.